An empirical correlation-based model to predict solid-fluid phase equilibria and phase separation of the ternary system CH4-CO2-H2S - Hani Ababneh (9218272) (2021)
To cover the expected increased demand for natural gas, energy industry has to exploit sour gas reserves located around the world. However, acid gases have to be removed before the natural gas produced from these fields could be used. One of the novel concepts in this field is the utilization of solid phase formation of carbon dioxide and/or hydrogen sulfide. The main aim of this study is to develop an empirical correlation model based on Peng-Robinson equation of state (PR EoS), with fugacity expressions, that is able for the first time to describe the solid-fluid phase equilibria for the ternary system of CH4-CO2-H2S at pressures from 5 to 30 bar and over a wide range of temperature (130–200 K). The model was first tested on the binary systems of CH4-CO2, CO2-H2S and CH4-H2S with optimized interaction parameters. When proven to be successful, it was then expanded in a predictive manner to describe the ternary system of CH4-CO2-H2S. The model predictions for the solidification points of 5 different mixtures were within the acceptable error when compared to the experimental data available in the literature. A model based on equilibrium stage separation unit was used to study the separation of three different feed compositions of this ternary system. Overall, it was found that separation of CO2 in solid phase improves when increasing the operating pressure up to 20 bar, and decreases at higher temperatures. Similarly, the separation of H2S in either liquid or solid phase improves at higher pressures and lower temperatures. The recovery of CH4 was high over the entire ranges of operating conditions, expect at high pressure (30 Bar) at temperatures below 190 K. This work provides scientists and engineers with an accurate tool that may be used with confidence for predicting solid-fluid phase equilibria. Consequently, this model eliminates difficulties associated with the need for experiments on ternary system solid-fluid phase equilibria. Other Information Published in: Journal of Natural Gas Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jngse.2021.104120